A low-dielectric and low-loss low-temperature co-fired ceramic / glass composite material
By using alumina and CBS microcrystalline glass phases in low-temperature co-fired ceramic technology and adding K2O, LiF, and Nb2O5, the firing temperature and dielectric loss of ceramic/glass composite materials have been successfully reduced, solving the problem of high dielectric loss in the existing technology, and achieving better dielectric performance.
Patent Information
- Application Number
- CN202410419053.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-04-09
AI Technical Summary
The fire temperature and dielectric loss of the existing low-temperature co-fired ceramic technology (LTCC) are still relatively high, making it difficult to meet the demand for low fire temperature and dielectric loss of microelectronic components.
Alumina (Al2O3) is used as the ceramic phase and CaO-B2O3-SiO2 (CBS) is used as the glass phase. By adding K2O, LiF, and Nb2O5, the sintering temperature and dielectric properties of the material are adjusted to prepare a low-dip and low-loss low-temperature co-fired ceramic/glass composite material.
The firing temperature of the ceramic/glass composite material is reduced to 800-875°C, the dielectric constant is reduced to 6.0-8.5, and the dielectric loss is reduced to 0.6×10-4-0.1×10-4 (1MHz), which significantly improves the performance of the material.
Smart Images

Figure CN118324497B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a low-dielectric and low-loss low-temperature co-fired ceramic / glass composite material. Background Art
[0002] In recent years, with the rapid development of communication technology, the needs of electronic equipment for miniaturization, portability, multi-function, digitization, high frequency, high reliability and high performance have promoted the development of electronic components in the direction of miniaturization, integration and high frequency. In this context, high temperature co-fired ceramic technology (HTCC) is increasingly unsuitable for the development of miniaturized electronic components due to its high resistivity, large electrical loss and large dielectric constant of substrate materials caused by the high firing temperature (generally around 1500°C). Low temperature co-fired ceramic technology (LTCC) is increasingly valued due to its low dielectric loss, high operating frequency (up to 40GHz), small size, high stability, etc., and it can form a three-dimensional structure by embedding capacitors and inductors inside the circuit, thereby greatly reducing the size of the circuit.
[0003] However, the firing temperature of existing LTCC is generally around 900-950℃, and there is still a certain degree of dielectric loss. For microelectronic components, the lowest possible ceramic firing temperature and dielectric loss are often pursued to reduce signal delay time, achieve frequency selectivity, and reduce the generation of inductive crosstalk and noise.
[0004] Based on this, a low-temperature co-fired ceramic with lower firing temperature and dielectric loss has become an urgent need in this field. Summary of the invention
[0005] In order to solve the above problems, the present application provides a low dielectric and low loss low temperature co-fired ceramic / glass composite material. 2 O 3 ) as ceramic phase, CaO-B 2 O 3 -SiO 2 (CBS) as a glass phase and through K 2 O, LiF, Nb 2 O 5 The addition of further reduces the firing temperature of the prepared low-temperature co-fired ceramic / glass composite material and at the same time has lower dielectric loss.
[0006] In order to achieve the above-mentioned object, the first technical solution of the present application discloses a low-temperature co-fired ceramic / glass composite material, which comprises, by weight:
[0007] CBS glass-ceramic: 30-50 parts;
[0008] Alumina: 50-70 parts;
[0009] Transition Metal Oxide Nb 2 O 5 : 3-9 parts;
[0010] Alkali metal compounds K 2 O: ≤1;
[0011] Fluoride LiF: ≤1.5 parts.
[0012] Wherein, the sum of the added amounts of the CBS glass-ceramics and alumina is 100 parts by mass.
[0013] Furthermore, the CBS glass-ceramics components include CaCO 3 : 35wt%-45wt%; H 3 BO 3 :20wt%-30wt%; SiO 2 :25wt%-35wt%.
[0014] The second technical solution of the present application discloses a method for preparing the above-mentioned low temperature co-fired ceramic / glass composite material, comprising:
[0015] Preparation of CBS glass-ceramic powder;
[0016] Mixed CBS glass-ceramic powder, alumina, and transition metal oxide Nb 2 O 5 , alkali metal compound K 2 O and fluoride LiF are mixed by alcohol ball milling and dried to obtain a low temperature co-fired ceramic / glass composite material.
[0017] Furthermore, the preparation of CBS glass-ceramics powder is as follows:
[0018] CaCO 3 , H 3 BO 3 、SiO 2 The mixed powder is melted at 1400-1500°C to obtain molten glass, which is then ground into glass powder after being cooled and formed.
[0019] And, a low temperature co-fired ceramic / glass composite material prepared according to the above preparation method.
[0020] The third technical solution of the present application discloses the application of the above-mentioned low-temperature co-fired ceramic / glass composite material in the preparation of microelectronic components. During the preparation, the sintering temperature of the low-temperature co-fired ceramic / glass composite material is 800-875°C.
[0021] The beneficial effects of the present invention are as follows: the present application provides a low temperature co-fired ceramic / glass composite material and a preparation method thereof, by 2O 3 ) as ceramic phase, CaO-B 2 O 3 -SiO 2 (CBS) as a glass phase and through K 2 O, LiF, Nb 2 O 5 The addition of 20% mol / l can reduce the firing temperature of the prepared low-temperature co-fired ceramic / glass composite material to 800-875°C when used to prepare microelectronic components, while reducing the dielectric constant to 6.0-8.5 and the dielectric loss to 0.6×10 -4 -0.1×10 -4 (1MHz). BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Attached Figure 1 It is a schematic diagram of the preparation process of the LTCC material in the present invention;
[0023] Attached Figure 2 This is a particle size distribution diagram of the CBS glass powder prepared in the present invention;
[0024] Attached Figure 3 This is a cross-sectional SEM image of the CBS glass-ceramics after sintering in the present invention. DETAILED DESCRIPTION
[0025] The scheme of the present invention is explained below in conjunction with embodiments. Those skilled in the art will understand that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention.
[0026] The first embodiment of the present application discloses a low temperature co-fired ceramic / glass composite material, which comprises, by weight:
[0027] CBS glass-ceramic: 30-50 parts;
[0028] Alumina: 50-70 parts;
[0029] Transition Metal Oxide Nb 2 O 5 : 3-9 parts;
[0030] Alkali metal compounds K 2 O: ≤1;
[0031] Fluoride LiF: ≤1.5 parts.
[0032] Wherein, the sum of the added amounts of the CBS glass-ceramics and alumina is 100 parts by mass.
[0033] In this embodiment, the alumina is used as a ceramic phase, and the CBS glass-ceramic is used as a glass phase. The prior art generally reduces the sintering temperature by adding glass. CBS glass-ceramic is a low-melting-point glass, but its sintering temperature is generally still above 900°C, and glass, as an introduced impurity, will increase the number of pores in the sintered body, thereby affecting the dielectric, thermal and mechanical properties of the ceramic. Therefore, the present application adopts CBS glass-ceramic as the glass phase. As a low-melting-point glass, it can reduce the sintering temperature to about 850°C, and has little effect on the dielectric properties. Furthermore, as a microelectronic device, it is often necessary to pursue the lowest possible sintering temperature and dielectric loss to reduce signal delay time, achieve frequency selectivity, and reduce the generation of inductive crosstalk and noise; therefore, the present application adds the transition metal oxide Nb 2 O 5 , alkali metal compound K 2 O, fluoride LiF, to improve the physical properties of uniform glass powder with D50 reaching 3μm.
[0034] Among them, K 2 O can reduce the softening point of glass, lower the sintering temperature, and promote the efficiency of liquid phase sintering; LiF and Nb 2 O 5 It can be used as a crystal nucleating agent to promote the formation of β-CaSiO in CBS glass-ceramics at a lower temperature. 3 Wollastonite phase, as an ideal crystal form, has excellent dielectric properties and good thermal stability. Among them, LiF can form a liquid phase during the sintering process, accelerating the densification of ceramic sintering, and Nb 2 O 5 The precipitation of the crystalline phase in CBS glass-ceramics can be controlled. The combined effect of the two reduces the generation of pores during the firing process, forming a dense low-temperature co-fired ceramic / glass composite material, which reduces the dielectric loss to 0.6×10 -4 -0.1×10- 4 (1MHz), maintaining a dielectric constant of 6.0-8.5; on the other hand, due to the LiF and Nb 2 O 5 As a crystal nucleating agent, it can promote the formation of crystal phase and reduce the crystallization temperature. Therefore, the combined effect of the three reduces the sintering temperature to 800-875℃, greatly improving the performance of low-temperature co-fired ceramic / glass composite materials.
[0035] The second embodiment of the present application discloses a method for preparing the above-mentioned low temperature co-fired ceramic / glass composite material, comprising:
[0036] Preparation of CBS glass-ceramic powder;
[0037] Mixed CBS glass-ceramic powder, alumina, and transition metal oxide Nb 2O 5 , alkali metal compound K 2 O, fluoride LiF is mixed by alcohol ball milling and dried to obtain a low temperature co-fired ceramic / glass composite material, as shown in the attached Figure 1 shown.
[0038] In the embodiment of the present application, the CBS glass-ceramics is CaCO 3 -H 3 BO 3 -SiO 2 Glass, the composition of which includes CaCO 3 : 35wt%-45wt%; H 3 BO 3 :20wt%-30wt%; SiO 2 :25wt%-35wt%, the sum of the three contents is 100%; It is understandable that the CBS glass-ceramics in the prior art also contains some trace dopants, such as P 2 O 5 ,Na 2 O, MgO, SrO, the present application preferably contains 35wt%-45wt% CaCO 3 , 20wt%-30wt%H 3 BO 3 , 25wt%-35wt%SiO 2 ;1wt%-2wt%MgO;1wt%-2wt%P 2 O 5 ; 0wt%-1wt%Na 2 O; the sum of the contents of the above is 100%.
[0039] In this embodiment, the addition of trace dopants can serve as a nucleating agent to promote the formation of crystal nuclei in the CBS glass-ceramic system, thereby achieving more excellent dielectric properties.
[0040] It can be understood that the preparation process of CBS microcrystalline glass is well known in the art. The preparation method of some specific embodiments of the present application is: the ingredients are prepared according to the above-mentioned component contents, and then a mixed powder is obtained by alcohol wet ball milling, drying, and sieving; the mixed powder is melted into glass liquid at 1400-1500°C for 24 hours, and then the mixed powder is cooled by water quenching to form a glass block, and then the glass block is broken into a slurry by a ball mill and then dried and sieved to obtain glass powder.
[0041] Figure 2 The powder particle size distribution diagram of CBS glass-ceramics in the glass / ceramic composite material of this embodiment shows a good normal distribution, wherein D10 is 0.829 μm, D50 is 2.363 μm, and D90 is 5.428 μm. The smaller particle size is conducive to full and uniform distribution around the ceramic phase.
[0042] Figure 3 The SEM microscopic morphology of the CBS glass-ceramic powder in the glass / ceramic composite material of this embodiment shows that the particles are small and uniform in morphology, with good uniformity and stability. During the sintering process, a liquid phase can be fully formed to wrap the alumina ceramic phase to promote sintering densification and effectively reduce the sintering temperature.
[0043] In some preferred embodiments, the glass powder is a uniform glass powder with a D50 of 3 μm.
[0044] In the embodiment of the present application, CBS glass-ceramics powder, aluminum oxide, and transition metal oxide Nb 2 O 5 , alkali metal compound K 2 O, fluoride LiF after mixing to obtain a low temperature co-fired ceramic / glass composite material is preferably: the above materials are placed in a nylon ball mill, zirconium balls and alcohol are added for wet mixing, the ball mill speed is 280r / min, the time is 6h, during which the ball mill flip time interval is 30min, 11 flips are required, and then drying is performed, and sieving (60 mesh) is obtained. It can be understood that those skilled in the art can make substitutions or improvements according to the above preparation method without exceeding the conventional cognition in the art, and each technical parameter can also be adjusted conventionally within the cognition.
[0045] The third embodiment of the present application discloses the use of the above-mentioned low temperature co-fired ceramic / glass composite material in the preparation of microelectronic components. During the preparation, the sintering temperature of the low temperature co-fired ceramic / glass composite material is 800-875°C.
[0046] In this embodiment, since the production raw materials of the low-temperature co-fired ceramic / glass composite material of the present application are cheap, the production cost is low, the preparation process is simple, and the prepared material has excellent dielectric properties, it can be used in the manufacture of microwave devices such as low-temperature co-fired ceramic systems (LTCC), multilayer dielectric resonators, microwave antennas, filters, etc., and has great application value in industry.
[0047] Next, the technical means and technical effects of the present application are described in detail with reference to the accompanying drawings.
[0048] Example 1 Preparation of low temperature co-fired ceramic / glass composite material
[0049] S1. CaCO 3 43.5wt%;H 3 BO 3 24.5wt%;SiO 2 28.5wt%;P 2 O 5 1.5wt%;MgO 1.5wt%;Na2 O 0.5wt% sampling was put into a planetary ball mill, and a nylon ball mill was used with zirconium balls inside. Anhydrous ethanol was used as the ball milling medium for thorough mixing. After the mixed slurry was dried, the powder was then put into a platinum crucible: the crucible with the built-in powder was put into a high-temperature furnace and kept warm at 1400°C for 4h to obtain a high-temperature molten glass liquid.
[0050] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven sizes. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0051] S3. The obtained CBS microcrystalline glass powder is mixed with alumina ceramic powder and other additives: alkali metal oxide potassium oxide; transition metal oxide niobium pentoxide; fluoride lithium fluoride according to the proportions in Table 1, and the ball milling time is 6 hours with anhydrous ethanol at a speed of 280r / min. The mixed slurry is dried to obtain a low-temperature co-fired ceramic / glass composite material.
[0052] Table 1
[0053] Components CBS Glass <![CDATA[Al 2 THE 3 ]]> <![CDATA[Nb 2 THE 5 ]]> <![CDATA[K 2 The]]> LiF Mass 35 65 5 0.2 0.5
[0054] A 5% PVA solution was added to the sieved composite powder for granulation. Then, it was dry pressed into a disc-shaped green body with a diameter of 12 mm and a thickness of about 1 mm through a mold. Then, it was placed in a muffle furnace for debinding and sintering: the debinding process was heated to 500°C at 1°C / min for 5 hours, and then heated to 850°C at 5°C / min for 1 hour for sintering. Test: The sintered ceramic sheet was silvered on both sides, and finally the performance of the disc was tested by an impedance analyzer 4291A: dielectric constant 6.90, dielectric loss 0.50×10 -3 (1MHz).
[0055] Example 2 Preparation of low temperature co-fired ceramic / glass composite material
[0056] S1. CaCO 3 35wt%;H 3 BO 3 28wt%;SiO 2 32.5wt%;P 2 O 5 2wt%;MgO2wt%;Na 2 O0.5wt% sampling is put into a planetary ball mill, and a nylon ball mill is used with zirconium balls inside. Anhydrous ethanol is used as the ball milling medium for thorough mixing. After the mixed slurry is dried, the powder is then put into a platinum crucible: the crucible with the built-in powder is put into a high-temperature furnace and kept warm at 1300°C for 4 hours to obtain a high-temperature molten glass liquid.
[0057] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven sizes. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0058] S3. The obtained CBS microcrystalline glass powder is mixed with alumina ceramic powder and other additives: alkali metal oxide potassium oxide; transition metal oxide niobium pentoxide; fluoride lithium fluoride according to the proportions in Table 2, and the ball milling time is 6 hours with anhydrous ethanol at a speed of 280r / min. The mixed slurry is dried to obtain a low-temperature co-fired ceramic / glass composite material.
[0059] Table 2
[0060] Components CBS Glass <![CDATA[Al 2 THE 3 ]]> <![CDATA[Nb 2 THE 5 ]]> <![CDATA[K 2 The]]> LiF Mass 45 55 3 0.5 1.35
[0061] A 5% PVA solution was added to the sieved composite powder for granulation. Then, it was dry pressed into a disc-shaped green body with a diameter of 12 mm and a thickness of about 1 mm through a mold. Then, it was placed in a muffle furnace for debinding and sintering: the debinding process was heated to 500°C at 1°C / min for 5 hours, and then heated to 800°C at 5°C / min for 1 hour for sintering. Test: The sintered ceramic sheet was silvered on both sides, and finally the performance of the disc was tested by an impedance analyzer 4291A: dielectric constant 8.27, dielectric loss 0.13×10 -3 (1MHz).
[0062] Example 3 Preparation of low temperature co-fired ceramic / glass composite material
[0063] S1. CaCO 3 41.5wt%;H 3 BO 3 22wt%;SiO 2 32.5wt%;P 2 O 5 1.5wt%;MgO 1.5wt%;Na 2 O 1wt% sampling is placed in a planetary ball mill, a nylon ball mill jar is used with zirconium balls, and anhydrous ethanol is used as the ball milling medium for thorough mixing. After the mixed slurry is dried, the powder is placed in a platinum crucible: the crucible containing the powder is placed in a high-temperature furnace and kept warm at 1350°C for 4 hours to obtain a high-temperature molten glass liquid.
[0064] S2. The obtained glass solution is poured into deionized water for cooling and quenching to obtain glass blocks of uneven sizes. The obtained glass blocks are crushed to obtain glass powder, thereby obtaining CBS microcrystalline glass powder with a particle size D50 of 3-4 μm.
[0065] S3. The obtained CBS microcrystalline glass powder is mixed with alumina ceramic powder and other additives: alkali metal oxide potassium oxide; transition metal oxide niobium pentoxide; fluoride lithium fluoride according to the proportions in Table 3, and the ball milling time is 6 hours with anhydrous ethanol at a speed of 280r / min. The mixed slurry is dried to obtain this low-temperature co-fired ceramic / glass composite material.
[0066] Table 3
[0067] Components CBS Glass <![CDATA[Al 2 THE 3 ]]> <![CDATA[Nb 2 THE 5 ]]> <![CDATA[K 2 The]]> LiF Quality score 40 60 9 0.2 0.25
[0068] A 5% PVA solution was added to the sieved composite powder for granulation. Then, it was dry pressed into a disc-shaped green body with a diameter of 12 mm and a thickness of about 1 mm through a mold. Then, it was placed in a muffle furnace for debinding and sintering: the debinding process was heated to 500°C at 1°C / min for 5 hours, and then heated to 875°C at 5°C / min for 1 hour for sintering. Test: The sintered ceramic sheet was silvered on both sides, and finally the performance of the disc was tested by an impedance analyzer 4291A: dielectric constant 8.10, dielectric loss 0.10×10 -3 (1MHz).
[0069] In summary, the low-temperature co-fired ceramic / glass composite material provided by the present invention has a significantly lower sintering temperature of 1500°C than that of alumina ceramic materials, and has a lower energy consumption. In addition, the dielectric constant of pure CBS microcrystalline glass at a sintering temperature of 850°C is 6.26, and the dielectric loss is 1.00×10 -3 (1MHz), the dielectric properties have been significantly improved, with excellent dielectric properties: dielectric constant 6.0-8.5, dielectric loss 0.6×10 -4 -0.1×10 -4 (1MHz). It has a wide range of applications and stable performance. It can be used to manufacture microwave components such as resonators, filters, dielectric ceramic substrates, etc. The preparation process is simple and can be industrialized and mass-produced.
[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a low temperature co-fired ceramic / glass composite material, characterized in that: include: Preparation of CBS glass-ceramic powder; CBS glass-ceramic powder is mixed with alumina, transition metal oxide Nb2O5, alkali metal compound K2O, and fluoride LiF, and then ball-milled and dried to obtain a low-temperature co-fired ceramic / glass composite material; The composite material component comprises: CBS glass-ceramic: 30-50 parts; Alumina: 50-70 parts; Transition metal oxide Nb2O5: 3-9 parts; Alkali metal compound K2O: ≤1 part; Fluoride LiF: ≤ 1.5 parts; The sum of the added amounts of the CBS glass-ceramics and alumina is 100 parts by mass; The raw materials for preparing the CBS glass-ceramics include CaCO3: 35wt%-45wt%; H3BO3: 20wt%-30wt%; SiO2: 25wt%-35wt%; The preparation of CBS microcrystalline glass powder is as follows: a mixed powder of CaCO3, H3BO3 and SiO2 is melted at 1400-1500°C to obtain glass liquid, and the mixture is cooled and formed and then ground into glass powder.
2. The low-temperature co-fired ceramic / glass composite material prepared according to the preparation method of claim 1.
3. The use of the low temperature co-fired ceramic / glass composite material in the preparation of microelectronic components according to claim 2, characterized in that: During preparation, the sintering temperature of the low temperature co-fired ceramic / glass composite material is 800-875°C.
Citation Information
Patent Citations
Low-temperature co-fired ceramic and preparation method thereof
CN112125652A
Calcium-boron-silicon LTCC (Low Temperature Co-Fired Ceramic) material and preparation method thereof
CN115466109A